2007
DOI: 10.4197/med.14-1.6
|View full text |Cite
|
Sign up to set email alerts
|

Successful Surgical Treatment of Mitral Valve Endocarditis Caused by Staphylococcus Lugdunensis

Abstract: Abstract. Staphylococcus lugdunensis, a very virulent coagulase negative species, has been recently recognized, and rarely reported in few cases, as a cause of endocarditis. This infection, in contrast to the ordinary staphylococcus epidermidis, is frequently lethal and carries a very high risk of devastating embolic complications. In this paper, it was reported that aggressive infection in a child presenting with mitral valve endocarditis, major left cerebral infarction, bulbar palsy and incontinence, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In all, nine patients were depicted including our case. [1][2][3][4][5][6] We excluded two cases because of incomplete data. The median age was 13 years [6.0-15.5] with five males.…”
Section: Resultsmentioning
confidence: 99%
“…In all, nine patients were depicted including our case. [1][2][3][4][5][6] We excluded two cases because of incomplete data. The median age was 13 years [6.0-15.5] with five males.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 original published articles were considered appropriate for inclusion in our review article (Figure 1 ). Out of these 17 studies, 16 were case reports from Italy [ 5 , 6 ], Switzerland [ 7 ], USA [ 8 - 11 ], UK [ 12 , 13 ], Morocco [ 14 ], Taiwan [ 15 , 16 ], Saudi Arabia [ 17 ], Spain [ 18 , 19 ], and Norway [ 20 ] while one case series was from Greece [ 21 ]. Koh et al had reported the first case of S. lugdunensis endocarditis-associated CVA from London, UK in 1996 [ 12 ].…”
Section: Reviewmentioning
confidence: 99%